Education and the evolution of comparative advantage. - Felipe, Jesus; Asian Development Bank (Manila,Philippines Asian Development Bank, [2021])
The results of the study are supported by analysis of the evolution of comparative advantage in 1,240 products from 49 low and middle income countries between 1995 and 2015. The evidence also shows that education appears unimportant for developing comparative advantage in products that are intrinsically complex or education intensive.
Keywords: Industry and state; Education -- Economic aspects; COVID-19,Disease; Electronic book